2020
DOI: 10.3390/pr8030265
|View full text |Cite
|
Sign up to set email alerts
|

Steel Wool for Water Treatment: Intrinsic Reactivity and Defluoridation Efficiency

Abstract: Studies were undertaken to characterize the intrinsic reactivity of Fe0-bearing steel wool (Fe0 SW) materials using the ethylenediaminetetraacetate method (EDTA test). A 2 mM Na2-EDTA solution was used in batch and column leaching experiments. A total of 15 Fe0 SW specimens and one granular iron (GI) were tested in batch experiments. Column experiments were performed with four Fe0 SW of the same grade but from various suppliers and the GI. The conventional EDTA test (0.100 g Fe0, 50 mL EDTA, 96 h) protocol was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 67 publications
0
18
0
Order By: Relevance
“…Therefore, "remediation using Fe 0 " is currently regarded as one of the best available technologies in the global effort to achieve Goal 6 of the UN Sustainable Development Goals (SDGs): Ensure availability and sustainable management of water and sanitation for all [14][15][16]. However, the Fe 0 remediation technology as a whole suffers from lack of reliable methods to characterize the intrinsic reactivity of used materials [17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, "remediation using Fe 0 " is currently regarded as one of the best available technologies in the global effort to achieve Goal 6 of the UN Sustainable Development Goals (SDGs): Ensure availability and sustainable management of water and sanitation for all [14][15][16]. However, the Fe 0 remediation technology as a whole suffers from lack of reliable methods to characterize the intrinsic reactivity of used materials [17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, a more rational approach is to consider that all species can be removed regardless of their redox potential, and identify exceptions on a case by case basis. In this regard, recent results by Hildebrant et al [140] have confirmed that fluoride removal is low, but less reactive materials (EDTA test) comparatively remove more fluoride. This last observation corroborates the view that there is no single Fe 0 material for all situations and calls for more systematic investigations to identify appropriate Fe 0 materials for specific remediation applications.…”
Section: Contaminant Removal Mechanismsmentioning
confidence: 93%
“…For example, while treating water in fluidized systems (Anderson Process), dense materials were better than sponge iron [13,168]. Similarly, Hildebrant et al [140] reported that Fe 0 materials of low reactivity according to the EDTA test exhibited a better efficiency for fluoride removal. The question arises how to select the right Fe 0 specimen for a given application?…”
Section: Selection and Characterization Of Fe 0 Materialsmentioning
confidence: 99%
See 2 more Smart Citations